2019
DOI: 10.1111/fwb.13428
|View full text |Cite|
|
Sign up to set email alerts
|

Can dispersal buffer against salinity‐driven zooplankton community change in Great Plains' lakes?

Abstract: 1. The North American Great Plains contains thousands of lakes that vary in salinity from freshwater to hypersaline. Paleolimnological studies show that salinity levels in these lakes are tightly linked with climate, and current projections point to a more arid future in the region due to natural and anthropogenic climate change, potentially influencing lake salinity.2. Many zooplankton species are sensitive to changes in salinity, and their position near the base of the aquatic food web makes it important to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Land use alterations (e.g., urbanisation, agriculture [49]) can change regional processes such as dispersal and impact regional species pools. However, FS has rarely been studied from a metapopulation and metacommunity perspective [57,58]. FS alters habitat suitability, which translates to altered connectivity between inhabitable patches.…”
Section: Regional and Landscape Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Land use alterations (e.g., urbanisation, agriculture [49]) can change regional processes such as dispersal and impact regional species pools. However, FS has rarely been studied from a metapopulation and metacommunity perspective [57,58]. FS alters habitat suitability, which translates to altered connectivity between inhabitable patches.…”
Section: Regional and Landscape Scalesmentioning
confidence: 99%
“…This can modify colonisation-extinction dynamics and/or favour the spread of salt tolerant, generalist species or invasive species [61,117]. Habitat connectivity plays a key role in environmental tracking (i.e., adaptation to environmental change at the community level) and therefore in either buffering (e.g., population maintenance due to mass effect) or favouring community differentiation (e.g., change in species pool) [57][58][59]. At the same time, connectivity may also contribute to negative impacts of FS by propagating it from a main source (e.g., basin-wide effects [118]) and this must therefore be considered since changes in the upstream chemical composition can be exported across a whole river catchment [119,120].…”
Section: Open Accessmentioning
confidence: 99%
“…In the published article, “Can dispersal buffer against salinity‐driven zooplankton community change in Great Plains' lakes?” by Huynh and Gray (2019), the order of text in the first column of Table 3 is incorrect. The correct order is “Passive” (first row) and then “Active” (second row) as shown in the table below.…”
Section: Dispersal Type Source Df Sum Of Squares Mean Square F Rmentioning
confidence: 99%
“…In addition, Coldsnow et al (2017) showed that freshwater Daphnia pulex could evolve to tolerate slightly elevated salt concentrations (0.1-1‰) after 5-10 generations. In theory, the evolutionary response of zooplankton could be accelerated by the dispersal of salinity-tolerant genotypes from surrounding lakes (Cottenie and De Meester 2003), but little research has examined if intraspecific differences in salinity tolerance exist in natural populations (Huynh and Gray 2020).…”
mentioning
confidence: 99%